Spontaneous spike signals originated from redox-active molecules functionalised on carbon nanotubes. (5th July 2019) - Goh, Kian Lian; Fujii, Hayato; Setiadi, Agung; Kuwahara, Yuji; Akai-Kasaya, Megumi
Abstract: Biological computing has always been an interesting and promising field due to its high optimisation and energy frugality in problem-solving. Frequency and timing of the neural spike signal define how the information processing works in biological neural networks. Here, we demonstrate that the addition of redox-active polyoxometalate (POM) molecules to carbon nanotube (CNT) parallel multi-junctions provides an interesting spike signal. The redox state of POM molecules at the junction between CNTs and metal electrodes contributes to the generation of spike signal merely by the use of small DC bias. However, the spike signal from the device was frequently disrupted by the phase transition in the output current. It was elucidated that the lifetime of redox state exhibited by POM is the principal determinant of spike signal generation in a CNT/POM network.